Neutral recycling effects on ITG turbulence. (4th July 2017) - Stotler, D.P.; Lang, J.; Chang, C.S.; Churchill, R.M.; Ku, S.
Abstract: The effects of recycled neutral atoms on tokamak ion temperature gradient (ITG) driven turbulence have been investigated in a steep edge pedestal, magnetic separatrix configuration, with the full- f edge gryokinetic code XGC1. An adiabatic electron model has been used; hence, the impacts of neutral particles and turbulence on the density gradient are not considered, nor are electromagnetic turbulence effects. The neutral atoms enhance the ITG turbulence, first, by increasing the ion temperature gradient in the pedestal via the cooling effects of charge exchange and, second, by a relative reduction in the E × B shearing rate.